Fundraising for regional environmental issues: Public perceptions of who is financially responsible for the local environment. Issue 3 (1st October 2020) - Jones, Jennifer A.; Bi, Xiang
Abstract : Environmental nonprofit organizations attract less than 5 % of total philanthropic giving. Given the seriousness of the environmental challenges facing the globe, it is imperative to identify barriers to and best practices in soliciting environmental giving. Past studies have identified the difficulty in soliciting funding for macro‐level environmental concerns or for concerns considered to be public goods; however, little research has been conducted about giving to regional environmental concerns. Our research questions were as follows: (a) from what type of sources do residents believe environmental protection for regional environmental concerns should be funded?; (b) how willing are residents to contribute financially to regional environmental concerns?; and (c) to what extent do residents trust nonprofit organizations to address regional environmental concerns? We surveyed Florida residents ( n  = 548) about the conservation of the Ocklawaha River and the breaching of the Rodman Reservoir, an area with pressing environmental concerns and heavily frequented for economic and recreational use. Findings suggest that (a) participants believe government agencies, not nonprofits, should fund restoration projects, (b) participants trust nonprofits more than government to accomplish restoration goals, and (c) participants are more interested in contributing via taxes than via donations. Considerations for fundraising are discussed.